(untitled) (Al-NASR, 2024)
Given the Social Cognitive Theory concept in global understanding, Employee Productivity through Artificial Intelligence can be tested in other contexts. It is research within the tertiary care hospitals of City Gujranwala (GTH (775 bedded) and GMCTH 502 bedded). The results shows that AI tools significantly & positively helps the management and give a road map to facilitate their routine tasks and healthcare professionals to ease their clinical and theoretical concepts by using AI tools. This study also explores the hypothesis and the mediating role of Organizational Support (OS), use of Information Technology (IT) and Employee Innovations. The data was collection from the tertiary care hospitals of Gujranwala from 165 doctors, management and supportive staff. Partial Least Squares (PLS) results shown that the research can be conducted in other tertiary care hospitals to examine its impact. Other research areas include expanding the theoretical model with other independent and dependent variables and to validate it in different organizational contexts to make out a clearer image of the relationships one during the testing.